Factors Affecting Pedicle Screw Insertional Torque in Spine Deformity Surgery. Issue 17 (1st September 2021) - Oda, Kotaro; Ohba, Tetsuro; Hiroshi, Yokomichi; Fujita, Koji; Tanaka, Nobuki; Koyma, Kensuke; Haro, Hirotaka
Abstract : Study Design: Retrospective observational study of consecutive patients. Objective: We sought to: (1) clarify the key factors predominantly associated with the insertional torque of pedicle screws; (2) compare the optimal factors for pedicle screw insertion to obtain rigid screw fixation in patients with adult spinal deformity (ASD) and in those with adolescent idiopathic scoliosis (AIS); (3) determine the optimal screw/pedicle ratio (S/P) to obtain rigid pedicle screw fixation. Summary of Background Data: Rigid pedicle screw fixation is mandatory to perform corrections for spinal deformities properly and to allow successful fusion after surgery. The fixation depends mainly on screw position accuracy and patient bone quality. Traditionally, spinal surgeons have decided the screw size, trajectory, and tapping size based on their intuition. Insertional torque has been indicated as useful to predict screw fixation strength, and is correlated with screw pullout strength and frequency of postoperative screw loosening. Methods: We compared insertion torque at L1–L3 levels of 324 screws in 68 patients with ASD and 58 screws in 32 patients with AIS. We assessed the association between screw/pedicle ratio and insertion torque by constructing a spline curve. Results: Pedicle and screw diameter correlated positively with insertion torque in patients with either ASD or AIS. The optimal screw/pedicle ratio to obtain rigid pedicle screw fixation in patients with ASD was close to, but less than one, and, by contrast, was about 1 to 1.25 in patients with AIS. Conclusion: We propose the concept of an optimal S/P ratio for obtaining rigid pedicle screw fixation during spinal corrective surgery, which is different for patients with ASD and patients with AIS. The S/P ratio is useful for deciding the appropriate diameter screw for each case in preoperative planning. Level of Evidence: 4 Abstract : This was a comparison study for insertion torque of pedicle screws in patients with adult spinal deformity and patients with adolescent idiopathic scoliosis. We propose the importance of the screw/pedicle ratio to obtain rigid pedicle screw fixation. The optimal ratio is different for each target disease.